Analyzing The Effectiveness of Social Media Marketing in PT Primajasa (Journal of Business and Management, 2022)
Nowadays, social media is the future of branding in marketing. Social media is used as the main tool in marketing to tell the product review to convey customer engagement. Social media in the digital area is a platform to conduct interaction and information together to accomplish business goals. The social media platform is an intermediary between brands and audiences and utilizes customer engagement to engage the product review. Mostly, the social media platform uses Instagram as their social media since it can easily go viral. PT Primajasa, the leading transportation sector in Indonesia, uses the Instagram page to integrate the companies and audiences and helps companies to see the story behind the campaign. Before customers take additional action to make a purchase, their Instagram pages show a lot of likes, comments, and shares from other users. Customers frequently make purchases on social media by highlighting the success of the business's social media performance. To get attention from people, Social Media content has to be creative and innovative in increasing customer engagement and product reviews of users. Content that consists of storytelling makes people more engaged and increases the achievement of purchase intention. Furthermore, this study aims to determine the effect of Social media Marketing, Product Review, and Customer Engagement on Purchase Interest in PT Primajasa's transportation services. This research is associative research and the type of data used is quantitative data. The sampling technique used was purposive sampling. The number of samples is 354 consisting of current passengers of PT Primajasa, students of the Management Study Program, Faculty of Economics and Business, Bandung Institute of Technology in 2022-2024 and employees of PT Primajasa in the field of Marketing. Data analysis used Multiple Linear Analysis. The results of this study answered the direct effect of Social Media Marketing on Customer Engagement and Purchase Intention. Indirect Social Media Marketing has more positive influences through Customer Engagement as a mediator than direct Social Media Marketing on Purchase Intention.